Peran Kearifan Lokal dalam Melestarikan Kain Ulos Sebagai Warisan dan Budaya Batak Toba - An Nisa Febrianti (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This research examines the role of local wisdom in preserving the Batak Toba ulos cloth as heritage and culture. The purpose of this study is to describe the values of local wisdom embedded in the Batak Toba ulos. The theory of local wisdom proposed by Robert Sibarani is used as the basis for data analysis. The data collection method used in this research is qualitative descriptive, and data is gathered through a literature review of various journals related to the topic. The preservation of the ulos cloth as a cultural heritage of the Batak Toba is greatly aided by local wisdom. Ulos is a symbol of tradition, identity, and values for the Batak people, beyond being just a fabric. Local wisdom helps maintain and pass down this cultural heritage through traditional weaving practices and the use of ulos in various traditional ceremonies. Therefore, ulos is one of Indonesia's cultural legacies that must be preserved, as it is a high-quality product of creative thought. The sacred value of ulos reflects the spirituality of the Batak people. Each ulos establishes a connection between the maker and the recipient. For an individual, ulos is a fabric that warms the body, but for the community, ulos has a symbolic role in various aspects of life. In addition to producing high-quality ulos, the ulos fabric should be kept in a clean and comfortable place, and it should be displayed properly so that visitors may become customers. Ulos is used in various traditional ceremonies as a symbol of identity, a form of respect, a gesture of affection, and a unifying bond.